2018
DOI: 10.1002/jemt.23074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a potentially erosive antiasthmatic medicine on the enamel and dentin of primary teeth: An in situ study

Abstract: This study evaluates, in situ, the effect of an anti‐asthmatic medicine on the enamel and dentin of primary teeth. Twenty‐eight specimens of enamel and dentin were prepared, selected, sterilized, and stored. Microhardness, microscopic morphology, and initial surface roughness were evaluated. Fourteen volunteers wore palatal devices containing two dentin specimens and two enamel specimens. Volunteers underwent surface treatment three times a day for 5 days, with the dripping of 5 ml of salbutamol sulfate for 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 27 publications
(46 reference statements)
0
5
0
5
Order By: Relevance
“…In children 6–12 years old, Rezende et al showed that there was a relationship between salbutamol usage and dental caries, although they could not find a relationship between asthma disease and caries, erosion and enamel defects (Rezende et al, 2019). Scatena et al reported that salbutamol sulfate has an erosive effect on primary tooth enamel, and this erosive effect can be observed morphologically in primary dentin (Scatena et al, 2018). Heidari et al found the relationship between asthma medications and the severity of dental caries, reported that this relationship is mainly due to the form of medications taken (e.g., tablet, spray‐inhaler, syrup) rather than different types of medications or combinations of them (Heidari et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children 6–12 years old, Rezende et al showed that there was a relationship between salbutamol usage and dental caries, although they could not find a relationship between asthma disease and caries, erosion and enamel defects (Rezende et al, 2019). Scatena et al reported that salbutamol sulfate has an erosive effect on primary tooth enamel, and this erosive effect can be observed morphologically in primary dentin (Scatena et al, 2018). Heidari et al found the relationship between asthma medications and the severity of dental caries, reported that this relationship is mainly due to the form of medications taken (e.g., tablet, spray‐inhaler, syrup) rather than different types of medications or combinations of them (Heidari et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Scatena et al reported that salbutamol sulfate has an erosive effect on primary tooth enamel, and this erosive effect can be observed morphologically in primary dentin (Scatena et al, 2018). Heidari et al found the relationship between asthma medications and the severity of dental caries, reported that this relationship is mainly due to the form of medications taken (e.g., tablet, spray-inhaler, syrup) rather than different types of medications or combinations of them (Heidari et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sustrato. Para comprender mejor los procesos involucrados en la erosión dental y poder revertir su efecto, se utilizan dientes extraídos, generalmente especímenes de esmalte o dentina de premolares o terceros molares permanentes (Hooper et al, 2014;West et al, 2019) o esmalte de dientes deciduos humanos (Scatena et al, 2018;Magalhães et al, 2009). Es importante considerar la edad del donante de los dientes; se ha demostrado que el esmalte dental natural maduro es menos susceptible a desafíos erosivos que el esmalte inmaduro ya que existen diferencias en el contenido mineral y las características de la superficie (West et al, 2011;Young & Tenuta;Yassen et al, 2011).Es así que se prefieren utilizar dientes premolares que terceros molares para este tipo de estudios, además es necesario la estandarización cuidadosa de la preparación de las muestras y la asignación al azar de las mismas, entre los participantes.…”
Section: Evaluación In Situunclassified
“…Los sustratos deben ser sometidos a procedimientos de desinfección y esterilización para garantizar especímenes estériles y seguros para los pacientes. Entre estos procedimientos se han utilizado con mayor frecuencia: solución acuosa de timol al 0,1 % (Hara et al, 2006;Turssi et al, 2010Turssi et al, , 2014Wiegand & Attin, 2014;Hara et al, 2014;Almeida;João-Souza et al;Scatena et al;de Souza et al), clorhexidina al 0,5 % durante 30 minutos (West et al, 2004;Hooper et al, 2007Hooper et al, , 2014Field et al;West et al, 2019), 2 % de formaldehído durante 30 días a pH 7 para la desin-fección de los dientes antes de su uso in situ (Rios et al, 2006(Rios et al, , 2008Magalhães et al;Rios et al, 2009) y para la esterilización óxido de etileno durante una hora a 55º C (Hara et al, 2006;Hooper et al, 2007;Turssi et al, 2010;Hara et al, 2014;Turssi et al, 2014;Almeida;Ruben et al, 2017;de Souza et al;Santos et al;Mendonça et al, 2019;Jordão et al, 2019;Rios et al, 2019). La esterilizacion con óxido de etileno es un procedimiento eficaz para dientes extraidos que no altera la dureza superficial, la respuesta a la desmineralización del esmalte y es de fácil acceso ya que es ampliamente utilizado en la esterilización de instrumental médico (Hara et al, 2006;West et al, 2011;Shellis et al;Wiegand & Attin, 2011).…”
Section: Evaluación In Situunclassified
See 1 more Smart Citation